2010
DOI: 10.1097/aog.0b013e3181e9e0ab
|View full text |Cite
|
Sign up to set email alerts
|

Oral Desipramine and Topical Lidocaine for Vulvodynia

Abstract: I.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
143
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 170 publications
(147 citation statements)
references
References 25 publications
1
143
0
3
Order By: Relevance
“…Other studies using lidocaine showed improvement in pain and sexual function. However, when comparing lidocaine to other treatments, its efficacy was found nonsignificantly different than biofeedback in the study of Danielsson et al [27] and desipramine and/or placebo in the study of Foster et al [28]. The latter's posology and technique of application differed from those of Zolnoun et al [26], which may explain the lower efficacy.…”
Section: Introductionmentioning
confidence: 89%
See 4 more Smart Citations
“…Other studies using lidocaine showed improvement in pain and sexual function. However, when comparing lidocaine to other treatments, its efficacy was found nonsignificantly different than biofeedback in the study of Danielsson et al [27] and desipramine and/or placebo in the study of Foster et al [28]. The latter's posology and technique of application differed from those of Zolnoun et al [26], which may explain the lower efficacy.…”
Section: Introductionmentioning
confidence: 89%
“…In the most conservative scenario, a sample of 170 participants (85 per group) would be necessary. To account for an expected drop-out rate of 20% after 6 months [18] and [28], 212 participants (170/0.80) need to be enrolled at baseline. This number provides sufficient power to meet the secondary objectives with power ranging from 84.4-99.9%.…”
Section: Sample Sizementioning
confidence: 99%
See 3 more Smart Citations